THE INFLUENCES OF PERCEIVED USEFULNESS AND ONLINE SOCIAL NETWORK ATTRIBUTE ON THE INTENTIONS TO SEEK AND SHARE INFORMATION ON INDONESIA’S SMART CITY DIGITAL PLATFORM - Rouli, Juliana (Journal of Environmental Science and Sustainable Development, 2021)
The high population and density of cities in Indonesia raise a number of urban problems that require creative and innovative solutions. One of the steps taken by the municipal government is to implement the concept of smart city, one of which is by utilizing information and communication technology (ICT). The municipal government applies ICT by creating websites and applications to provide a variety of city information and municipal government services to all residents that can also be shared on their online social network. However, it is not clear whether the residents perceive that the provided information is useful and whether the intentions to seek and share information from smart city platform are influenced by the perceived usefulness of the information and the citizen’ online social network attributes. Hence, this study was conducted with the aim to analyze the effect of the perceived usefulness of smart city information and social network attributes (number of ties and diversity of ties) on intention to seek and share information on smart city websites and applications in cities in Indonesia. The data were collected using a survey method, involving 1,161 respondents in 8 major cities in Indonesia, namely Jakarta, Bandung, Surabaya, Semarang, Medan, Makassar, Denpasar, and Banjarmasin. The survey results were analyzed using partial least square structural equation modeling (PLS-SEM), and it is concluded that the perceived usefulness of smart city information and the residents’ online social network attributes have positive and significant effects on the intention to seek information and intention to share information on smart city websites and apps.